2015
DOI: 10.1002/tox.22187
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin induces DNA damage and inhibits DNA repair associated protein expressions in NCI-H460 human lung cancer cells

Abstract: Nonsmall cell lung carcinoma (NSCLC) is a devastating primary lung tumor resistant to conventional therapies. Bisdemethoxycurcumin (BDMC) is one of curcumin derivate from Turmeric and has been shown to induce NSCLC cell death. Although there is one report to show BDMC induced DNA double strand breaks, however, no available information to show BDMC induced DNA damage action with inhibited DNA repair protein in lung cancer cells in detail. In this study, we tested BDMC-induced DNA damage and condensation in NCI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Cell nucleus was stained with PI (red fluorescence). Leica TCS SP2 Confocal Spectral Microscope was used to examine and photomicrography as described previously . Co‐localization of cytochrome c or AIF in nuclei or cytosol was formed yellow color based on red and green overlapped pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Cell nucleus was stained with PI (red fluorescence). Leica TCS SP2 Confocal Spectral Microscope was used to examine and photomicrography as described previously . Co‐localization of cytochrome c or AIF in nuclei or cytosol was formed yellow color based on red and green overlapped pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we add the DAPI solution (1 μg/mL) at 37 °C without light. Nuclear morphologies were photographed using a fluorescence microscope (Eclipse TE 300, Nikon, Tokyo, Japan) as described previously [45].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were placed in 6-well plate at a density of 2 × 10 5 cells/well and cells were incubated with 18α-GA ranging from 40–120 μM for 48 h. After treatment, cells from each treatment were harvested to examine the DNA damage with the Comet assay as described previously [45].…”
Section: Methodsmentioning
confidence: 99%
“…(1) is decreased and DNA damage is increased after BDMC (35 μM) treatment in a timedependent manner. Moreover, the proteins levels of 14-3-3r, MGMT, BRCA1, and MDC1 were found to be decreased in human lung cancer NCI-H460 cells following treatment with BDMC while the levels of p-p53 and p-H2A.X were increased (Yu, Yang, Huang et al, 2015).…”
Section: Lung Cancermentioning
confidence: 92%
“…Yu et al explored the impact of BDMC treatment on DNA damage and condensation in NCI‐H460 cells and found that viable cell count (1) is decreased and DNA damage is increased after BDMC (35 μM) treatment in a time‐dependent manner. Moreover, the proteins levels of 14‐3‐3r, MGMT, BRCA1, and MDC1 were found to be decreased in human lung cancer NCI‐H460 cells following treatment with BDMC while the levels of p‐p53 and p‐H2A.X were increased (Yu, Yang, Huang et al, ). S‐phase is the part of the cell cycle in which DNA is replicated, occurring between G1 and G2 phase.…”
Section: Lung Cancermentioning
confidence: 99%